Aerofoil optimization using SLSQP and validation using numerical and analytical methods - Srinath R.,; R., Mukesh; Inamul Hasan,; P., Radha Krishnan (Vietnam Journal of Science and Technology, 2024)
Aircraft design optimization is one among the research enriched topic in the aerospace industry, with enhancing aircraft performance, safety, and efficiency numerous being the prime focus areas. The work done demonstrates the application of the Sequential Least Squares Programming (SLSQP) technique over a symmetrical aerofoil “NACA 0012” to improve its aerodynamic performance. The optimized aerofoil is validated using Design and Analysis Tools for Composite Aircraft (DATCOM) and Computational Fluid Dynamics (CFD) methods. The study focuses on optimizing the performance of a symmetric aerofoil, where drag minimization is crucial, subject to list constraints, such as in the design of fuel-efficient aircraft. The results reveal, the optimized aerofoil has a significant reduction in drag coefficient of closer to 11 % between 8° and 10° compared to the initial design. The validation using DATCOM and CFD methods confirms the accuracy and usefulness of the optimization results. Validation error values are found to be negligible when compared to the optimization data, coming in at 5.7% and 6.5% for DATCOM and CFD, respectively. The paper highlights that the SLSQP technique is efficient and reliable optimization method for designing high-performance aerofoils.